EFIKASI DIRI DALAM HUBUNGANNYA DENGAN NIAT KARYAWAN UNTUK BERPINDAH KERJA - Mustika Tarigan (Universitas Trisakti, 2011)
The purpose of this research is to analize the relationship between self effication and switching intention. The research uses 120 samples having similar characteristic the the subject of the research. Hypothesis test in this research uses multiple regressions analysis. The results shows no significant relationship between self effication and switching intention. Hopefully the next research will study the various level/ job position such as staff, lecturer or other fields of work in which the job requires the thinking ability more than energy. It is advisable to add more variables that may influent the switching intention that has not been studied in the curent research such as work satisfaction, work stress, organizational commitment, type of leadership.Keywords: Self effication, Switching intention